Предмет: Алгебра,
автор: angelina3730
Решите уравнение
2m+m(3-(m-1))=m(2-m)
Ответы
Автор ответа:
1
2m+m(3-m+1)=2m-m²;
2m+m(4-m)=2m-m²;
2m+4m-m²=2m-m²; -m² и 2m сокращаются
4m=0;
m=0.
ответ: 0.
2m+m(4-m)=2m-m²;
2m+4m-m²=2m-m²; -m² и 2m сокращаются
4m=0;
m=0.
ответ: 0.
Автор ответа:
1
2m+m×(3-m+1)=2m-m^2
2m+m×(4-m)=2m-m^2
2m+4m-m^2=2m-m^2
4m=0
m=0÷4
m=0
2m+m×(4-m)=2m-m^2
2m+4m-m^2=2m-m^2
4m=0
m=0÷4
m=0
Похожие вопросы
Предмет: Алгебра,
автор: lesi4ka6
Предмет: Химия,
автор: financemnkiboyqy3e
Предмет: История,
автор: nata1508111
Предмет: Математика,
автор: ollga82